Environmental Impacts of Commercial Haulage Operations on Air Quality in Nigeria - Oyelami, Seun; Oyewo, Abideen Temitayo; Ibiyemi, Praise Oluwatobiloba; Oyewole, Kehinde Adenike; Okedere, Oyetunji Babatunde; Olamide Lateef Ogunsesan; Adegbola, James Obafemi; Ajayi, Samuel Adebanji (International Journal of Integrated Engineering, 2025)
The operation of large haulage vehicle parks in Nigeria significantly contributes to ambient air pollution, posing serious environmental and health risks. This study investigates the adverse environmental consequences of air pollutants released by haulage vehicles in a major highway park connecting Osun state to other parts of Nigeria. Focusing on Oke Ese, Ilesha, Nigeria, the research identifies primary pollutants, measures concentrations, and analyzes air quality impacts. Total Suspended Particulates (TSP) and X-ray Fluorescence (XRF) analyses were conducted across various sample sites, including the truck park and surrounding residential areas. Findings reveal that Total Suspended Particulate (TSP) concentrations range from 83.14 ?g/m3 to 720.59 ?g/m3, exceeding Nigerian air quality standards and posing health risks to nearby residents. Average ambient sampling values were 404.86 ?g/m3, significantly higher than the FEPA standard of 250 ?g/m3. Source Sampling and residential sampling averages were 990.2?g/m3 and 235.29 ?g/m3, respectively. XRF analysis detected high levels of magnesium in truck exhaust, with a maximum value of 189.25106 ×106 (µg/m³), far exceeding the US National Ambient Air Quality Standard (NAAQS) of 100 µg/m³. The study concludes that stricter emission regulations and alternative energy solutions are necessary to mitigate environmental and public health impacts. Achieving recommended air quality guidelines could save millions of lives globally, emphasizing the importance of addressing air pollution. The research underscores the need for urgent action to protect the health and well-being of communities surrounding haulage vehicle parks in Nigeria.